2004
DOI: 10.1093/sjaf/28.4.196
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in the Microfibril Angle of Loblolly Pine From Two Test Sites

Abstract: In recent years, several studies have examined the effect of microfibril angle (MFA) on wood quality. However, little research has been conducted upon the genetic mechanisms controlling MFA. In this study, we examined the heritability of MFA in loblolly pine, Pinus taeda L.,and its genetic relationships with height, diameter, volume, and specific gravity. Increment cores were collected at breast height from 20 to 25 progeny from each of 12 to 17 crosses (among 11 parents) in two modified partial-diallels in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The environmental effect on MFA increased with tree age. Myszewski et al (2004) found significant, but unspecified, environmental influences on MFA in P. taeda. Jordan et al (2006Jordan et al ( , 2007 found significant site variation, also in P. taeda, but could not relate this to any specific site factor other than growth rate.…”
Section: Site and Silviculturementioning
confidence: 87%
See 3 more Smart Citations
“…The environmental effect on MFA increased with tree age. Myszewski et al (2004) found significant, but unspecified, environmental influences on MFA in P. taeda. Jordan et al (2006Jordan et al ( , 2007 found significant site variation, also in P. taeda, but could not relate this to any specific site factor other than growth rate.…”
Section: Site and Silviculturementioning
confidence: 87%
“…Clark and Daniels (2004) found that specific gravity and MFA have a strong inverse correlation in P. taeda, attributed to increased amounts of latewood, which has reduced MFA. Interestingly, Myszewski et al (2004), also working on P. taeda, found no such correlation. In P. radiata clones, Lindström et al (2005) found that clones with high MOE, and hence lower MFA compared to low-MOE clones, had longer tracheids (1.8 mm cf.…”
Section: Relationships Between Mfa and Cell Dimensionsmentioning
confidence: 94%
See 2 more Smart Citations
“…An inverse relationship between MFA and cell length is generally accepted and has been reported in a number of studies [21][22][23]. However, reports are not consistent across the scientific literature as some authors argue that tracheid length is not related to MFA [24,25] while Evans et al [26] demonstrated a clear correlation between MFA, density and fibre cell wall thickness. On balance, these data suggest that cell length is possibly mediated by microtubules; however, since MFA is an important feature of SCW formation, it is unlikely that it influences cell size after cell elongation has ceased.…”
Section: Mfa As a Key Feature Of Scw Formationmentioning
confidence: 99%